2005
DOI: 10.1038/ng1679
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoid cell growth and transformation are suppressed by a key regulatory element of the gene encoding PU.1

Abstract: Tight regulation of transcription factors, such as PU.1, is crucial for generation of all hematopoietic lineages. We previously reported that mice with a deletion of an upstream regulatory element (URE) of the gene encoding PU.1 (Sfpi1) developed acute myeloid leukemia. Here we show that the URE has an essential role in orchestrating the dynamic PU.1 expression pattern required for lymphoid development and tumor suppression. URE deletion ablated B2 cells but stimulated growth of B1 cells in mice. The URE was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
211
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(229 citation statements)
references
References 50 publications
14
211
4
Order By: Relevance
“…Recent data has shown that deletion of PU.1 in B cells can induce a B-2 to B-1 cell switch, accompanied by loss of B220 expression (27). In addition, deletion of a regulatory element upstream of the PU.1 gene eliminates B-2 cells, but enhances the B-1 cell population (58). Our data indicate that pro-B cells ectopically expressing Spi-C have dramatically reduced levels of B220 on their surface, which could suggest that these cells may be switching to a B-1 cell phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data has shown that deletion of PU.1 in B cells can induce a B-2 to B-1 cell switch, accompanied by loss of B220 expression (27). In addition, deletion of a regulatory element upstream of the PU.1 gene eliminates B-2 cells, but enhances the B-1 cell population (58). Our data indicate that pro-B cells ectopically expressing Spi-C have dramatically reduced levels of B220 on their surface, which could suggest that these cells may be switching to a B-1 cell phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…This balance is tipped during commitment, with the silencing of the phase 1 regulatory genes and down-regulation of Kit, but only limited aspects of this process are understood. GATA-3, Runx1, and TCF-1 (or its relative LEF-1) eventually play roles in silencing expression of phase 1 regulatory genes encoding PU.1 and Bcl11a during commitment, as demonstrated by gain-and loss-offunction data (27,(36)(37)(38)(39) (Fig. 1B).…”
Section: T-cell Specification Grn Transitions At Commitment: a Distinctmentioning
confidence: 99%
“…36,38,39 Conditional deletion of the PU.1 gene in adult bone marrow progenitors showed its requirement for both monocyte and lymphoid progeny whereas granulocyticlike cells were increased indicating that PU.1 may inhibit adult in vivo granulopoiesis at latter stages of development. 34,40 Similarly, PU.1 has only a minor function in advanced differentiation states of B cells 25,34,35,[41][42][43] and is not required in mature T cells. [44][45][46] Collectively the above-mentioned facts reveal an important and crucial role of PU.1 as a primary transcriptional determinant of hematopoietic cell fate with current evidence showing its substantial role in the cell fate control of HSC and progenitor populations rather than the maturation of terminally differentiated cells.…”
Section: Pu1 and Its Role In Hematopoiesismentioning
confidence: 99%
“…24,25,80,81,82 Targeted disruption of the URE in mice significantly reduces PU.1 expression and results in the development of acute myeloid leukemia with frequent cytogenetic aberrations. 24 The URE structure is dynamically regulated by chromatin loops associated with the chromatin remodeling regulator SATB1 bound directly to the URE.…”
Section: Gata-1 and Pu1 Levels Are Determinants Of Leukemogenesismentioning
confidence: 99%
See 1 more Smart Citation